2016
DOI: 10.1080/02757540.2015.1120722
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bacterial quorum-sensing inhibitors against the formation of the diatom-biofilm

Abstract: Quorum-sensing inhibitor (QSI) is one of the most promising and environmentally friendly agents for marine antifouling. In this study, the activities of three kinds of QSIs 3,4-dibromo-2(5)Hfuranone, 4-nitropyridine-N-oxide and indole were evaluated on the growth of two marine diatoms Cylinthrotheca sp. and Nitzschia closterium. At the same time, the effects of QSIs on the formation of the diatom-biofilm were also discussed. All the results showed that QSIs significantly inhibited the growth, and the effects d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…This species is deeply studied for its extracellular polymeric substances, its adhesion mechanisms and its relationships with bacteria [ 36 , 37 , 38 ]. It is able to form mixed biofilm with bacterial strains and a possible role of bacterial signal molecules AHL in the formation of its biofilm has been indicated [ 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This species is deeply studied for its extracellular polymeric substances, its adhesion mechanisms and its relationships with bacteria [ 36 , 37 , 38 ]. It is able to form mixed biofilm with bacterial strains and a possible role of bacterial signal molecules AHL in the formation of its biofilm has been indicated [ 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that Ca 2+ might be involved in the mobility, attachment and growth of diatoms [ 43 ]. Moreover, a recent study has shown the effect of QS inhibitors on the growth and the diatom biofilm formation [ 40 , 41 ]. Thus, several mechanisms could explain the impact of DBHB on diatoms biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…AHLs also have effect on diatoms in the biofilm matrix as was observed by Yang et al [94]. 3,4-dibromo-2(5)H-furanone,4-nitropyridine-N-oxide and indole were able to decrease significantly the growth of two marine diatoms, Cylindrotheca sp.…”
Section: Macroalgal Colonization and Chemical Interactionsmentioning
confidence: 53%
“…While natural quorum sensing-inhibiting compounds have been widely isolated from a large diversity of living organisms, their effects on marine biofilms remain poorly explored. One reason is that these compounds are produced at low concentrations, which limits their application in the environment (Yang et al, 2016). However, synthetic quorum sensing-inhibiting compounds can now be used.…”
Section: Applications For Biofouling On Marine Underwater Surfacesmentioning
confidence: 99%